Expatriate Workers and Its Repercussions on the Economy and Labor Market in Iraq After 2003 - Dawood, Yusur Qasim Abdulhameed; Salih, Lorance Yahia (Journal of Economics and Administrative Sciences, 2021)
The demand for expatriate labor to Iraq increased after 2003 as a result of the openness that Iraq experienced, but this expatriate labor, which was requested at an increasing rate, has had economic, social, and political effects on the Iraqi economy in general, and the Iraqi labor market in particular. This is due to the high rates of unemployment, as most of these expatriate workers cause competition to local labor, and thus cause repercussions on the Iraqi economy as a whole, except for those expatriate workers coming with companies working in the oil sector. Iraq’s GDP